1977
DOI: 10.1128/aac.11.4.725
|View full text |Cite
|
Sign up to set email alerts
|

Cefoxitin Resistance to Beta-Lactamase: a Major Factor for Susceptibility of Bacteroides fragilis to the Antibiotic

Abstract: Toluene-treated cell suspensions of Bacteroides fragilis were used to screen clinical isolates for the production of f3lactamase. Approximately one-third of the isolates possessed considerable cephalosporinase activity. A significant correlation was found between f3lactamase production and resistance to cephalosporin antibiotics. Several isolates were resistant to cefuroxime and cefamandole and produced enzymes capable of hydrolyzing these antibiotics. However, none of the 79 strains tested could hydrolyze the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
26
1

Year Published

1978
1978
1989
1989

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(29 citation statements)
references
References 21 publications
2
26
1
Order By: Relevance
“…On the other hand, new N-lactamase inhibitors such as clavulanic acid and CP-45899 had no affinity to the enzyme from P. morganii GN5407. These substrate specificities of P. morganii GN5407 cephalosporinase prove to be close to those reported for cephalosporinases from E. coli GN5482,2p) E. cloacae GN7471,21) C. freundii GN7391,22> S. marcescens GN10857, P. aeruginosa GN10362 and P. rettgeri GN4430.23) DARLAND et al 32) have shown that cefoxitin was an effective inhibitor against B. fragilis ,3-lactamase, but cefuroxime was hydrolyzed by the R-lactamase from B. fragilis. Studies in our laboratory also proved that cefuroxime-type cephalosporins were well hydrolyzed by the ~-lactamase from B. fragilis GN-1147725) and moreover, those from P. vulgaris GN791924> and P. cepacia GN11164.18) In addition the hydrolysis of cephalothin by (3-lactamases from B. fragilis, P. vulgaris and P. cepacia was competitively inhibited by both clavulanic acid and CP-45899.…”
Section: Characterization Of Cephalosporinasesupporting
confidence: 51%
“…On the other hand, new N-lactamase inhibitors such as clavulanic acid and CP-45899 had no affinity to the enzyme from P. morganii GN5407. These substrate specificities of P. morganii GN5407 cephalosporinase prove to be close to those reported for cephalosporinases from E. coli GN5482,2p) E. cloacae GN7471,21) C. freundii GN7391,22> S. marcescens GN10857, P. aeruginosa GN10362 and P. rettgeri GN4430.23) DARLAND et al 32) have shown that cefoxitin was an effective inhibitor against B. fragilis ,3-lactamase, but cefuroxime was hydrolyzed by the R-lactamase from B. fragilis. Studies in our laboratory also proved that cefuroxime-type cephalosporins were well hydrolyzed by the ~-lactamase from B. fragilis GN-1147725) and moreover, those from P. vulgaris GN791924> and P. cepacia GN11164.18) In addition the hydrolysis of cephalothin by (3-lactamases from B. fragilis, P. vulgaris and P. cepacia was competitively inhibited by both clavulanic acid and CP-45899.…”
Section: Characterization Of Cephalosporinasesupporting
confidence: 51%
“…Of the currently available beta-lactam antibiotics, cefoxitin has the best in vitro activity (4,19). The enhanced activity of cefoxitin against these pathogens has been attributed to the resistance of the drug to the beta-lactamases of B. fragilis (3,5,7,11,22). Although there have been rare reports documenting the inactivation of the drug, the most common reported mechanism of cefoxitin resistance in this group of organisms has been the failure of the drug to penetrate through the outer membrane (6).…”
mentioning
confidence: 99%
“…Changes in the chemical structure of the cephalosporins have resulted in an increased antibacterial spectrum, more useful pharmacokinetic properties, and, in some cases, a high level of resistance to fi-lactamase hydrolysis. The presence of fi-lactamases in gram-negative organisms has been associated with resistance to cephalosporins, although these enzymes are not the only factor contributing to the resistance of gram-negative bacilli to f3-lactam compounds (3,9,10,15). There is great interest in antibiotics that are resistant to fl-lactamase hydrolysis and in compounds that are inhibitors of 8B-lactamases (2,5,11 (11).…”
mentioning
confidence: 99%
“…Recently, naturally occurring inhibitors of ,B-lactamases produced by streptomyces have been discovered (1,14). Cefoxitin and cefuroxime, two new fi-lactam compounds, have been reported to be resistant to B8-lactamases of gram-negative bacilli (3,12).…”
mentioning
confidence: 99%